Autophagy and Its Implications Against Early Full Nutrition Support in Critical Illness. (17th April 2018) - Van Dyck, Lisa; Casaer, Michaël P.; Gunst, Jan
Abstract: The timing, dose, and route of early nutrition support in critically ill patients have been highly controversial for years. Despite the association of a caloric deficit with adverse outcome, several recent large, randomized, controlled trials have demonstrated a prolongation of organ failure and increased muscle weakness with increasing doses of nutrition in the acute phase of critical illness. A potential explanation for the negative impact of early, full feeding on outcome is feeding‐induced suppression of autophagy, a cellular repair process that is necessary to clear intracellular damage. Whether nutrition management in critically ill patients should be guided by its effects on autophagy is a topic of debate. Currently, however, autophagy cannot be monitored in clinical practice. Moreover, clinical management should be guided by high‐quality randomized controlled trials, which currently do not support the use of early full nutrition support.